ANALYSIS OF THE MAIN CHARACTER NEEDS IN LIFE OF PI MOVIE USING MASLOW’S THEORY - Truman AM, Yohanes; Kuncara, Singgih Daru; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2017)
This research focuses on analyzing the Hierarchy of Needs manifested in the main character. Two questions were designed to discuss this topic. The first question is about the Needs manifested by the main character in the movie. The second question is about the desire of the main character in fulfilling his Needs. This research used descriptive qualitative method to explain and describe the data carefully in answering the questions. The data in this research were in written form taken from the dialogue and narration of the movie. This research uses Maslow’s theory. it is appropriate theory to this research. This research examines the elements of the hierarchy of needs through the main character. Keywords: Life of Pi, Maslow, hierarchy of need.